Kvasidegeneroituneiden steriilien neutriinojen havaitseminen - Oravasaari, Tero (2013)
We study a model of sterile neutrinos where the three ordinary active neutrinos actually consist of a superposition of an active and a sterile neutrinos forming quasidegenerate pairs. Oscillation between these pairs causes mixing between active and sterile neutrinos. Eigenmasses of the quasidegenerate pairs are very close to each other and theirs mass squared difference is of the order δm2 ~ 10^-12 eV2 or less. Such a small mass squared difference could be probed with AGN and GRB neutrinos detected in cubic kilometer size neutrino observatories.